Exploring Environmental Sustainability Through the Lens of Seyyed Hossein Nasr: A Scientific Perspective on Nature and Ecological Challenges - Daryono; Setiawati, Rini (Analisis Data Innovation, 2024)
Objective: This mixed research aims to explore Seyyed Hossein Nasr's environmental philosophy and its relationship to modern ecological issues in Indonesia, specifically examining how spirituality and indigenous ecological understanding can shape environmental governance.Methods: Employing a hybrid methodology, the study utilized questionnaires and interviews with 190 diverse participants, including officials, advocates, local people, and experts. It analyzed foundational perspectives, noting similarities and differences influencing attitudes and practices regarding the environment.Results: The findings prominently align Nasr's nature reverence with participants' spiritual connections to nature. Additionally, incorporating traditional environmental knowledge into policy was found to strengthen community participation and promote sustainable behavior. However, modern governance's secularization often undermines spiritual viewpoints, generating challenges.Novelty: This unique research presents an examination of the intersections between spirituality, indigenous ecological knowledge, and contemporary environmental policymaking in Indonesia, providing a fresh perspective on ecological ethics informed by Nasr's philosophy.Implication: The study suggests that decision-makers can leverage insights from spirituality and traditional ecological knowledge to develop more all-inclusive and impactful sustainability strategies, fostering a harmonious human relationship with nature.